α-Calcitonin gene-related peptide inhibits autophagy and calpain systems and maintains the stability of neuromuscular junction in denervated muscles - Machado, Juliano; Silveira, Wilian A.; Gonçalves, Dawit A.; Schavinski, Aline Zanatta; Khan, Muzamil Majid; Zanon, Neusa M.; Berriel Diaz, Mauricio; Rudolf, Rüdiger; Kettelhut, Isis Do Carmo; Navegantes, Luiz Carlos Carvalho (Molecular metabolism, 2019)
OBJECTIVE: Although it is well established that a-calcitonin gene-related peptide (CGRP) stabilizes muscle-type cholinergic receptors nicotinic subunits (AChR), the underlying mechanism by which this neuropeptide regulates muscle protein metabolism and neuromuscular junction (NMJ) morphology is unclear. - METHODS: To elucidate the mechanisms how CGRP controls NMJ stability in denervated mice skeletal muscles, we carried out physiological, pharmacological, and molecular analyses of atrophic muscles induced by sciatic nerve transection. - RESULTS: Here, we report that CGRP treatment in vivo abrogated the deleterious effects on NMJ upon denervation (DEN), an effect that was associated with suppression of skeletal muscle proteolysis, but not stimulation of protein synthesis. CGRP also blocked the DEN-induced increase in endocytic AChR vesicles and the elevation of autophagosomes per NMJ area. The treatment of denervated animals with rapamycin blocked the stimulatory effects of CGRP on mTORC1 and its inhibitory actions on autophagic flux and NMJ degeneration. Furthermore, CGRP inhibited the DEN-induced hyperactivation of Ca2+-dependent proteolysis, a degradative system that has been shown to destabilize NMJ. Consistently, calpain was found to be activated by cholinergic stimulation in myotubes leading to the dispersal of AChR clusters, an effect that was abolished by CGRP. - CONCLUSION: Taken together, these data suggest that the inhibitory effect of CGRP on autophagy and calpain may represent an important mechanism for the preservation of synapse morphology when degradative machinery is exacerbated upon denervation conditions.
Im Titel ist "Alpha" als griechischer Buchstabe dargestellt
Gesehen am 02.01.2020